The role of attachment type and bone height in modulating stress distribution in mandibular overdentures: Insights from finite element analysis - Burç İhsan Gencel; Melahat Çelik Güven; Uğur Mercan; Süleyman Çağatay Dayan; Onur Geçkili (PLoS ONE, 2026)
Background Mandibular two-implant overdentures are considered the standard of care for edentulous patients. The attachment system and the shape of the bone crest can significantly influence biomechanical behaviours. This study aimed to evaluate stress distribution in mandibular implant-supported overdentures using locator and bar attachments across various bone crest designs. Materials and methods FEA was performed on mandibular overdentures supported by two implants. Three crest configurations (flat, convex, and irregular) were modelled with either bar or locator attachments. A vertical force of 100 N was applied in three loading conditions: anterior, unilateral molar, and bilateral molar. Maximum von Mises stresses and principal stresses were assessed. Results Anterior loading resulted in the highest stresses across all groups, with peak values reaching 12 N/mm² in the convex and irregular models. Bilateral molar loading consistently produced the lowest and most uniform stress distributions, while unilateral loading caused intermediate stress concentrations on the working side. Uneven platforms significantly increased stress levels, particularly under unilateral bar loading. Locator attachments showed slightly reduced stresses after bilateral loading in irregular crest configurations. Stress concentrations were primarily localized at the implant neck and prosthetic connectors. Conclusion Stress distribution in mandibular overdentures is significantly influenced by loading direction, crest shape, and attachment mechanism. Anterior loading poses the highest biomechanical risk, while bilateral posterior loading provides optimal conditions. Vertical discrepancies in implant platforms heighten stress concentrations, underscoring the importance of careful surgical planning. Locator attachments offer limited biomechanical advantages in uneven crest scenarios, supporting their use in anatomically challenging cases.